2018
DOI: 10.1038/s41467-018-03755-2
|View full text |Cite
|
Sign up to set email alerts
|

The beta secretase BACE1 regulates the expression of insulin receptor in the liver

Abstract: Insulin receptor (IR) plays a key role in the control of glucose homeostasis; however, the regulation of its cellular expression remains poorly understood. Here we show that the amount of biologically active IR is regulated by the cleavage of its ectodomain, by the β-site amyloid precursor protein cleaving enzyme 1 (BACE1), in a glucose concentration-dependent manner. In vivo studies demonstrate that BACE1 regulates the amount of IR and insulin signaling in the liver. During diabetes, BACE1-dependent cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 66 publications
3
88
0
Order By: Relevance
“…VAD is known to play a critical pathophysiological role in clinical metabolic syndrome and type 2 diabetes. Interestingly, a recent study reported that the amount of biologically insulin receptor active is regulated by the cleavage of its ectodomain, by the β-site amyloid precursor protein cleaving enzyme 1 (BACE1), in a glucose concentration-dependent manner 22 . They demonstrated that BACE1 (an aspartyl protease, not serine protease) regulated the cleavage of insulin receptor and insulin signaling mainly in db/db mouse livers 22 .…”
Section: Discussionmentioning
confidence: 99%
“…VAD is known to play a critical pathophysiological role in clinical metabolic syndrome and type 2 diabetes. Interestingly, a recent study reported that the amount of biologically insulin receptor active is regulated by the cleavage of its ectodomain, by the β-site amyloid precursor protein cleaving enzyme 1 (BACE1), in a glucose concentration-dependent manner 22 . They demonstrated that BACE1 (an aspartyl protease, not serine protease) regulated the cleavage of insulin receptor and insulin signaling mainly in db/db mouse livers 22 .…”
Section: Discussionmentioning
confidence: 99%
“…During diabetes, β-secretase-dependent cleavage of IR is increased and the amount of IR in the liver is reduced [11]. It was observed that infusion of a β-secretase inhibitor leads to partial restoration of the liver IR [11,12].…”
Section: Inhibition Of α-Glucosidase Ptp1b and β-Secretase And Antiomentioning
confidence: 99%
“…During diabetes, β-secretase-dependent cleavage of IR is increased and the amount of IR in the liver is reduced [11]. It was observed that infusion of a β-secretase inhibitor leads to partial restoration of the liver IR [11,12]. Aminostyrylbenzofurans, for example, have previously been found to display better inhibitory activities (IC 50 = 0.07-0.53 µM) than curcumin with an IC 5o value of 0.80 µM [12].…”
Section: Inhibition Of α-Glucosidase Ptp1b and β-Secretase And Antiomentioning
confidence: 99%
See 1 more Smart Citation
“…It is not only the altered protein levels and altered volume of regions in brain but also the expression and activity of enzymes which regulate the pathology of diabetes associated AD. The β secretase enzyme which is involved in cleavage of amyloid precursor protein (APP), and in the formation of Aβ plaque; is also involved in cleavage of insulin receptor which strengthens the link between Alzheimer's and diabetes (Meakin et al, ). Also, soluble APP β (sAPPβ) which is a product of enzyme β secretase is a major determinant in case of insulin resistance (Botteri et al, ).…”
Section: Tie‐ups Between Diabetes Mellitus and Alzheimer'smentioning
confidence: 99%